A loss-of-function variant in ZCWPW1 causes human male infertility with sperm head defect and high DNA fragmentation - Yuelin Song; Juncen Guo; Yanling Zhou; Xingjian Wei; Jianlan Li; Guohui Zhang; Hongjing Wang (Reproductive Health, 2024)
Abstract Background Male infertility is a global health issue. The more causative genes related to human male infertility should be further explored. The essential role of Zcwpw1 in male mouse fertility has been established and the role of ZCWPW1 in human reproduction needs further investigation to verify. Methods An infertile man with oligoasthenoteratozoospermia phenotype and his parents were recruited from West China Second University Hospital, Sichuan University. A total of 200 healthy Han Chinese volunteers without any evidence of infertility were recruited as normal controls, while an additional 150 infertile individuals were included to assess the prevalence of ZCWPW1 variants in a sporadic male sterile population. The causative gene variant was identified by Whole-exome sequencing and Sanger sequencing. The phenotype of the oligoasthenoteratozoospermia was determined by Papanicolaou staining, immunofluorescence staining and electron microscope. In-vitro experiments, western blot and in-silicon analysis were applied to assess the pathogenicity of the identified variant. Additionally, we examined the influence of the variant on the DNA fragmentation and DNA repair capability by Sperm Chromatin Dispersion and Neutral Comet Assay. Results The proband exhibits a phenotype of oligoasthenoteratozoospermia, his spermatozoa show head defects by semen examination, Papanicolaou staining and electron microscope assays. Whole-exome sequencing and Sanger sequencing found the proband carries a homozygous ZCWPW1 variant (c.1064C > T, p. P355L). Immunofluorescence analysis shows a significant decrease in ZCWPW1 expression in the proband’s sperm. By exogenous expression with ZCWPW1 mutant plasmid in vitro, the obvious declined expression of ZCWPW1 with the mutation is validated in HEK293T. After being treated by hydroxyurea, MUT-ZCWPW1 transfected cells and empty vector transfected cells have a higher level of γ-H2AX, increased tail DNA and reduced H3K9ac level than WT-ZCWPW1 transfected cells. Furthermore, the Sperm Chromatin Dispersion assay revealed the proband’s spermatozoa have high DNA fragmentation. Conclusions It is the first report that a novel homozygous missense mutation in ZCWPW1 caused human male infertility with sperm head defects and high DNA fragmentation. This finding enriches the gene variant spectrum and etiology of oligoasthenoteratozoospermia.